Cervical Lymphadenopathy in Ibadan, Nigeria. (2017)
Aim: To determine the pattern and causes of lymph node enlargement of cervical region in Ibadan, Nigeria. Materials and Methods: A 10-year (2003-2012) retrospective study was conducted on all head and neck lymph node biopsies received at the Department of Pathology, University College Hospital, Ibadan, Nigeria. Results: A total of 101 lymph node biopsies of cervical region were received within this period of study. 59.4% cases were seen in Males. Second decade of life has the highest number of cases (22.8%) followed by 3rd decade (17.8%). The common cause of cervical lymphadenopathy include non - specific hyperplasia, tumour metastasis and Non Hodgkin’s lymphoma seen in 27 (26.7%), 22 (21.8%) and 20 (19.8%) respectively. Granulomatous and Hodgkin’s Lymphoma constitute 17 (16.8%) and 11 (10.9%) respectively. The granulomatous causes were all due to tuberculosis. A single case of Rosai-Dorfman disease was seen in a male in the 3rd decade of life. Conclusion: This study shows that metastatic tumours, Hodgkins lymphoma and Non Hodgkins lymphoma constituting 52.4% of all cases of cervical lymphadenopathy are common in this environment therefore highlighting the need for early and proper evaluation of patients.